How COVID-19 is Affecting Firms in Indonesia : Results from the 1st Round of the COVID-19 Business Pulse Survey, June 15, 2020-June 23, 2020 - Doarest, Aufa; Kamphuis, Bertine (World Bank, Washington, DC, 2020)
This brief presents findings from the first round of a survey of 850 firms in Indonesia. The survey was implemented through phone interviews and found that Coronavirus 2019 (COVID-19) has had pronounced effects on Indonesia’s private sector. To help the private sector during this crisis, the government needs to improve the effectiveness of its support through better communication and easier access to support programs.